Pengaruh Baby Massage Dengan Minyak Essensial Mawar Terhadap Kualitas Tidur Bayi Usia 6 – 12 Bulan Di BPM Rahayu - Handayani, Welly; Nisa, Setia (Universitas Negeri Gorontalo, 2025)
This study aimed to determine the effect of baby massage using rose essential oil on the sleep quality of infants aged 6–12 months at BPM Rahayu. This research employed a pre-experimental design with a one-group pretest–posttest approach. The sample consisted of 15 infants selected using accidental sampling. Infant sleep quality was measured before and after the intervention using a structured sleep quality questionnaire. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed that before the intervention, all infants (100%) had moderate sleep quality, whereas after the intervention, all infants (100%) experienced good sleep quality. Statistical analysis revealed a significant difference in sleep quality before and after the intervention (p = 0.000 0.05). These findings indicate that baby massage combined with rose essential oil has a significant effect on improving sleep quality in infants aged 6–12 months. Baby massage with rose essential oil can be applied as an effective non-pharmacological intervention to support optimal infant growth and development.